Polyelectrolyte membranes for acid gas separations - Quinn, R.; Laciak, D.V.
New facilitated transport membranes have been synthesized and shown to selectively permeate carbon dioxide and hydrogen sulfide from methane and hydrogen. The membranes are based on the polyelectrolyte poly(vinylbenzyltrimethylammonium fluoride), PVBTAF, and exhibit exceptional permselective properties. For example, at 23°C and 32 cmHg CO2, a PVBTAF composite membrane displayed a CO2 permeance of 6xl0-6cm3/cm2scmHg and CO2/H2 and CO2/CH4 selectivities of 87 and 1000, respectively. The CO2/H2 selectivity is the highest reported for any membrane. The permeance of both CO2 and H2S increased with decreasing feed partial pressure of the respective gases, a characteristic of facilitated transport membranes. The permselectivity is also dependent on the hydration state of the membrane and is optimal at a gas stream relative humidity in the range 0.25-0.50. The membranes show no deterioration after 30 days of continuous operation but react with trace level sulfur-containing contaminants common to cylinder H2S.
Keywords: GAS SEPARATIONS; FACILITATED TRANSPORT; POLYELECTROLYTE MEMBRANES; CARBON DIOXIDE